Peran Mata Pelajaran Perpustakaan Sekolah dalam Meningkatkan Minat Baca Siswa di SMP Swasta YPI Nurul Hadina - Suci Dahlya; Khay Ratu Nisa; Erni Khairunisa; Chairunnisa Chairunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
Children's interest in reading in Indonesia is still a big challenge, although there are many efforts to improve it. Many factors influence, such as lack of access to interesting books, more dominant gadget play habits, and also an environment that is less supportive of reading habits. However, children's interest in reading in Indonesia can grow if they are introduced to relevant and interesting books, and encouraged to read from an early age. To foster an interest in reading, children need to be given the opportunity to find the type of reading that suits their interests and age. Books that are exciting and easy to understand can be a bridge so that they are more interested in reading. In addition, a supportive school and family environment, such as providing special time to read and discuss books, also plays a very important role in fostering positive reading habits. This research is qualitative with informants from the Principal and supporting informants for librarians, teachers and students at Nurul Hadina Junior High School. Data were collected using observation, interviews and documentation. The results of the study show that Nurul Hadina Junior High School plays an active role in increasing students' interest in reading through the school library. The role of the subjects in this library is (1) teaching how to find information, (2) improving writing skills, (3) helping independent learning, (4) improving reading habits, (5) helping with schoolwork, (6) critical thinking skills.